The Role of Motivation Work on Competence Work, Workload and Discipline Work on Work Performance in Kepulauan Riau Province - Mon, Muhammad Donal; Bestari, Muhammad Wahyudi Dwi (Dinasti Publisher, 2025)
This study aims to examine, analyze, and empirically demonstrate the influence of Competence (X1), Workload (X2), and Discipline (X3) on Work Performance (Y) in Kepulauan Riau Province Government with Motivation (Z) as a mediating variable. The sample size consisted of 317 employees in the Kepulauan Riau Province Government. The results of this study indicate that there is a direct influence of Competence on Work Performance, but it does not have a significant influence on Motivation. Workload does not have a significant influence on Work Performance but has a significant influence on Motivation. Discipline has a significant influence on Work Performance and has a significant influence on Motivation. Meanwhile, Motivation has a significant influence on Work Performance. Motivation cannot mediate between Competence and Work Performance. The indirect influence of Motivation cannot mediate between Competence and Work Performance. Motivation can mediate between Workload and Work Performance. Motivation can mediate between Discipline and Work Performance. This study is expected to provide an appropriate workload, increase motivation and work discipline, and continue to develop employee competencies that will have a positive impact on improving employee performance.